A further investigation of the centroid‐to‐centroid method for stereotactic lung radiotherapy: A phantom study. Issue 10 (11th September 2013) - Lu, Bo; Samant, Sanjiv; Mittauer, Kathryn; Lee, Soyoung; Huang, Yin; Li, Jonathan; Kahler, Darren; Liu, Chihray
Abstract : Purpose: : Our previous study [B. Lu et al., "A patient alignment solution for lung SBRT setups based on a deformable registration technique, " Med. Phys. 39(12), – (2012)] 10.1118/1.4766875 proposed a deformable‐registration‐based patient setup strategy called the centroid‐to‐centroid (CTC) method, which can perform an accurate alignment of internal‐target‐volume (ITV) centroids between averaged four‐dimensional computed tomography and cone‐beam computed tomography (CBCT) images. Scenarios with variations between CBCT and simulation CT caused by irregular breathing and/or tumor change were not specifically considered in the patient study [B. Lu et al., "A patient alignment solution for lung SBRT setups based on a deformable registration technique, " Med. Phys. 39(12), – (2012)]10.1118/1.4766875 due to the lack of both a sufficiently large patient data sample and a method of tumor tracking. The aim of this study is to thoroughly investigate and compare the impacts of breathing pattern and tumor change on both the CTC and the translation‐only (T‐only) gray‐value mode strategies by employing a four‐dimensional (4D) lung phantom. Methods: : A sophisticated anthropomorphic 4D phantom (CIRS Dynamic Thorax Phantom model 008) was employed to simulate all desired respiratory variations. The variation scenarios were classified into four groups: inspiration to expiration ratio (IE ratio) change, tumor trajectory change, tumor position change, tumor size change, and the combination of these changes. For each category the authors designed several scenarios to demonstrate the effects of different levels of breathing variation on both of the T‐only and the CTC methods. Each scenario utilized 4DCT and CBCT scans. The ITV centroid alignment discrepancies for CTC and T‐only were evaluated. The dose‐volume‐histograms (DVHs) of ITVs for two extreme cases were analyzed. Results: : Except for some extreme cases in the combined group, the accuracy of the CTC registration was about 2 mm for all cases for both the single and the combined scenarios. The performance of the CTC method was insensitive to region‐of‐registration (ROR) size selections, as suggested by the comparable accuracy between 1 and 2 cm expansions of the ROR selections for the method. The T‐only method was suitable for some single scenarios, such as trajectory variation, position variation, and size variation. However, for combined scenarios and/or a large variation in the IE ratio, the T‐only method failed to produce reasonable registration results (within 3 mm). The discrepancy was close to, or even greater than, 1 cm. In addition, unlike the CTC method, the T‐only method was sensitive to the ROR size selection. The DVH analysis suggested that a large ITV to PTV margin should be considered if a breathing pattern variation is observed. Conclusions: : The phantom study demonstrated that the CTC method was reliable for scenarios in which breathing pattern variation was involved. The T‐only gray value method worked for some scenarios, but not for scenarios that involved an IE ratio variation. For scenarios involving position variation, the T‐only method worked only with a careful selection of the ROR, whereas the CTC method was independent of ROR size as long as the ITVs were included in the ROR. One indication of the dose consequence analysis was that a large ITV to PTV margin should be considered if a breathing pattern variation is observed.